Multiple Forms of Cardiac Myosin-binding Protein C Exist and Can Regulate Thick Filament Stability - Kulikovskaya, Irina (The Rockefeller University Press, 2007)
Although absence or abnormality of cardiac myosin binding protein C (cMyBP-C) produces serious structural and functional abnormalities of the heart, function of the protein itself is not clearly understood, and the cause of the abnormalities, unidentified. Here we report that a major function of cMyBP-C may be regulating the stability of the myosin-containing contractile filaments through phosphorylation of cMyBP-C. Antibodies were raised against three different regions of cMyBP-C to detect changes in structure within the molecule, and loss of myosin heavy chain was used to monitor degradation of the thick filament. Results from Western blotting and polyacrylamide gel electrophoresis indicate that cMyBP-C can exist in two different forms that produce, respectively, stable and unstable thick filaments. The stable form has well-ordered myosin heads and requires phosphorylation of the cMyBP-C. The unstable form has disordered myosin heads. In tissue with intact cardiac cells, the unstable unphosphorylated cMyBP-C is more easily proteolyzed, causing thick filaments first to release cMyBP-C and/or its proteolytic peptides and then myosin. Filaments deficient in cMyBP-C are fragmented by shear force well tolerated by the stable form. We hypothesize that modulation of filament stability can be coupled at the molecular level with the strength of contraction by the sensitivity of each to the concentration of calcium ions.